PROFESIONALISME APARATUR SIPIL NEGARA (ASN) DI KANTOR CAMAT BUKIT RAYA KOTA PEKANBARU - prihati, prihati; harsini, harsini; nasution, sri roserdevi (Jurnal Niara, 2016)
The Indonesian people are always faced with the problem of how to build a clean government and good (good governance and clean government ) . Bureaucracy is expected to be a motivator and as well as a catalyst of the passing of development, not able to perform its role as a modern bureaucracy not only promote the capacity to organize the tasks and functions of the organization , but also capable of responding to the aspirations of the public into the activities and programs of the organization and is able to bring new innovations aimed at facilitate the performance of the organization and as a part of the manifestation of the professional apparatus. In the perspective of public administration Indonesia known to a wide range of pathologies that make bureaucrats or officials are not professional in their duties and functions include low motivation to change and innovate. Given the urgency of the apparatus role in organizing role and function , it would need to be sought and formulated a strategic approach to build the new face of professional personnel that are reliable , responsive , flexible and innovative in providing services and procedural development implementation.This type of research is descriptive qualitative approach , data collection techniques using in-depth interviews and documentation . The selection of informants by using purposive sampling so didapatlah informants in accordance with the criteria. Further analysis of the data through the interpretation of ethics and EMIC is further elaborated in the study of governance in accordance with the governance discussion is being investigated.The results of the study of responsiveness and innovation apparatus Subdistrict Bukitraya well in order to give service to the community as well as in the implementation of the tasks that others have started to lead to the vision of districts Bukitraya namely the realization of the District Bukitraya The Professionals In The Governance and Service to Society , it's just not done optimally.